2019
DOI: 10.3390/vetsci6010025
|View full text |Cite
|
Sign up to set email alerts
|

Flaxseed and Carbohydrase Enzyme Supplementation Alters Hepatic n-3 Polyunsaturated Fatty Acid Molecular Species and Expression of Genes Associated with Lipid Metabolism in Broiler Chickens

Abstract: Flaxseed is rich in α-linolenic acid and is used in broiler chicken diets to enrich tissues with n-3 fatty acids (FA). However, non-starch polysaccharides (NSP) in flaxseed decreases nutrient digestibility and limits the availability of n-3 FA. Addition of carbohydrase enzymes to flaxseed-based diets can decrease the anti-nutritive effects of NSP. We hypothesized that flaxseed and enzyme supplementation affect lipid content and alter expression of genes related to lipid metabolism in broiler liver. Five day-ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 44 publications
3
23
0
Order By: Relevance
“…These findings are in agreement with Cowieson and Ravindran, (2008) who found enhancements in the digestibility of lysine, methionine, cysteine, and threonine when a multiple enzyme mixture possessing protease, Xyl, and amylase was used to supplement corn-based diets, but these improvements did not affect the amino acid contents in muscle. Furthermore, Head et al (2019) reported that dietary αlinolenic acids in the form of linseed resulted in a significant increase of hepatic n-3PUFA; however, the inclusion of a multiple enzyme complex of Xyl and amylase in a linseed-based diet resulted in a reduction in the n-6PUFA-like linoleic acid, but oleic and linolenic acids were not affected. Muscle Thiobarbituric acid reactive substance (TBARS) concentration was decreased by reducing the energy in diets and this agreed with (Cho and Kim 2013;Haščík et al 2015;Saleh et al 2019; who observed that muscle MDA concentration was decreased in low-energy density diets supplemented with or without β-mannanase and Xyl supplementation in pigs.…”
Section: Resultsmentioning
confidence: 99%
“…These findings are in agreement with Cowieson and Ravindran, (2008) who found enhancements in the digestibility of lysine, methionine, cysteine, and threonine when a multiple enzyme mixture possessing protease, Xyl, and amylase was used to supplement corn-based diets, but these improvements did not affect the amino acid contents in muscle. Furthermore, Head et al (2019) reported that dietary αlinolenic acids in the form of linseed resulted in a significant increase of hepatic n-3PUFA; however, the inclusion of a multiple enzyme complex of Xyl and amylase in a linseed-based diet resulted in a reduction in the n-6PUFA-like linoleic acid, but oleic and linolenic acids were not affected. Muscle Thiobarbituric acid reactive substance (TBARS) concentration was decreased by reducing the energy in diets and this agreed with (Cho and Kim 2013;Haščík et al 2015;Saleh et al 2019; who observed that muscle MDA concentration was decreased in low-energy density diets supplemented with or without β-mannanase and Xyl supplementation in pigs.…”
Section: Resultsmentioning
confidence: 99%
“…The results revealed that enzyme addition to diets supplemented with 10% flaxseed decreased arachidonic acid and total long chain n-6 FA. Dietary flaxseed and enzyme treatments upregulated PPARα target genes CPT1A and ACOX1 while reducing the expression of de novo FA synthesis-related genes (76). In addition, Seidavi et al (77) demonstrated that supplementing the diet with probiotic/enzyme mixture had no effect on the humoral response against AI and FIGURE 2 | Micrograph of the bursa of Fabricius of broiler at day 28 of age stained with H&E (×40) to compare the follicle diameter in different groups; the distance between two follicular polar as shown all groups by lines: (A) broiler fed with low density diet supplemented with 0.1% of multienzyme; (B) broiler fed with a diet supplemented with 0.2% of multienzyme.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, dietary composition intervention with enzymes was recently studied by Head et al (76) who suggested that if broilers are supplemented with flaxseed, the nutrient digestibility and the availability of n-3 FA will be limited due to the presence of non-starch polysaccharides (NSP), by affecting the genetic process during lipid metabolism in the liver. The results revealed that enzyme addition to diets supplemented with 10% flaxseed decreased arachidonic acid and total long chain n-6 FA.…”
Section: Discussionmentioning
confidence: 99%
“…The author attributed the pattern of breast muscle fatty acid composition to the diet's fatty acid profile, confirming that poultry has a limited ability to transform dietary fat. There are reports of fatty acids manipulation in meat and eggs using dietary fat, alteration in production practices, antioxidants including vitamin E and ginseng (Hargis & Elswyk, 1993;Wood & Enser, 1997;Yan et al, 2011;Cherian, 2016;Head et al, 2019). Wood & Enser (1997) observed quick poultry meat response to dietary concentrations of linoleic, linolenic and total PUFA.…”
Section: Fatty Acid Compositionmentioning
confidence: 99%
“…Dietary recommendations of ECM are variable, ranging from 50-300 g/kg (Sundu et al, 2006;Diarra et al, 2014;Devi & Diarra, 2017) depending on the species, age and class of poultry. There have been studies on nutrient utilisation in broilers fed high fibre by-products using enzyme supplementation and probiotics (Sayehban et al, 2015;Sayehban et al, 2016;Seidavi et al, Head et al, 2019). Several techniques improve poultry ECM utilisation, such as amino acid and enzyme supplementation (Sundu et al, 2009;Diarra et al, 2014), diet composition (Devi & Diarra, 2017), and processing methods (Sundu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%